Touch of Dead Sookie Stackhouse: the complete stories - Harris, Charlaine (New York : Ace Books, 2009)
A collection of every short story featuring Sookie Stackhouse, the telepathic waitress heroine of the best-selling Southern Vampire novels.
Fairy dust -- Dracula night -- Word answer -- Lucky -- Gift wrap.
Keywords: Vampires; Occult fiction, American